A Digital Interface ASIC for Triple-Axis MEMS Vibratory Gyroscopes - Lv, Risheng (Sensors (Basel), 2020)
This paper proposes a solution for sensing spatial angular velocity. A high-performance digital interface application specific integrated circuit (ASIC) for triple-axis micro-electromechanical systems (MEMS) vibratory gyroscopes is presented. The technique of time multiplexing is employed for synergetic stable drive control and precise angular velocity measurement in three separate degrees of freedom (DOF). Self-excited digital closed loop drives the proof mass in sensing elements at its inherent resonant frequency for Coriolis force generation during angular rotation. The analog front ends in both drive and sense loops are comprised of low-noise charge-voltage (C/V) converters and multi-channel incremental zoom analog-to-digital converters (ADC), so that capacitance variation between combs induced by mechanical motion is transformed into digital voltage signals. Other circuitry elements, such as loop controlling and accurate demodulation modules, are all implemented in digital logics. Automatic amplitude stabilization is mainly realized by peak detection and proportion-integration (PI) control. Nonlinear digital gain adjustment is designed for rapid establishment of resonance oscillation and linearity improvement. Manufactured in a standard 0.35-μm complementary metal-oxide-semiconductor (CMOS) technology, this design achieves a bias instability of 2.1°/h and a nonlinearity of 0.012% over full-scale range.